Revitalization Of Cultural Heritage: A Holistic Approach To Local Wisdom Management In Panji Festival Events In Panji Village Buleleng - I Nengah Wirata; I Putu Esa Widaharthana; Luh Putu Citrawati; I Gede Sumadi; IGA. Ratih Asmarani (Eduvest - Journal of Universal Studies, 2025)
This article discusses efforts to revitalize cultural heritage through a holistic approach in managing local wisdom, especially in the context of the Panji Festival Event in Panji Village, Buleleng. Cultural heritage is an important asset in maintaining the identity and cultural desires of a society. However, cultural heritage is often neglected and threatened with extinction due to modernization and social change. To maintain the sustainability of cultural heritage, a holistic approach is needed that involves various aspects such as community participation, environmental preservation, education and local economic development. This article aims to explore a holistic approach in managing local wisdom to revitalize cultural heritage, with a focus on implementation at the Panji Festival in Panji Village, Buleleng. This research methodology includes a qualitative approach with data collection through participant observation, in-depth interviews with local stakeholders, as well as document analysis related to festival activities and cultural preservation efforts at the local level. The research results show that a holistic approach in managing local wisdom through the Panji Festival event has succeeded in building awareness of the importance of cultural heritage for local communities. The active participation of the community in organizing the festival, the integration of modern technology to promote and preserve local culture, as well as efforts to preserve the environment as an important aspect of festival activities have increased appreciation of cultural heritage and improved local economic prosperity.